Foot-and-mouth disease reproduction number: a scoping review - Gunasekera, Umanga; VanderWaal, Kimberly; Arzt, Jonathan; Perez, Andres (Frontiers in Veterinary Science, 2025)
IntroductionApproximately two-thirds of the countries worldwide are considered to be foot and-mouth disease (FMD) infected according to the World Organization for Animal Health (WOAH). The effective reproduction number (Re) is an important indicator to assess disease spread and evaluate the impact of preventive and control measures for FMD and other infectious diseases. Re is defined as the number of secondary infections caused by one infected animal in a susceptible population, accounting for maternal immunity, immunity from previous infections, and vaccination. When estimated at the farm/ herd level or above, this parameter is identified with terms such as Rh or Rf (commonly identified as R in this study).MethodsThis study reviews the values of R estimated for FMD globally using empirical data at the farm/herd level or above. The population, intervention, comparison, and outcome (PICO) criteria were used to search different databases and to identify relevant studies, resulting in the identification of 10 peer-reviewed articles from eight different countries within the past 20 years (1994–2024).Results and discussionRegardless of the diversity of epidemiological scenarios, the R-value of FMD remained from 0 to 13.3 with a median value of 1.68 for above farm level transmission. Results here summarize the expected range of values for R under different epidemiological conditions, contributing to the design and evaluation of prevention and control strategies and, ultimately, mitigating the impact of one of the most impactful livestock diseases worldwide. This review highlights the necessity of further studies due to a limited number of studies calculating R for FMD using empirical data.